2016
DOI: 10.3390/brainsci6040056
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Intermittent Theta-Burst Stimulation and Motor Control Training in Individuals with Cervical Dystonia

Abstract: Background: There is emerging evidence that cervical dystonia is a neural network disorder with the cerebellum as a key node. The cerebellum may provide a target for neuromodulation as a therapeutic intervention in cervical dystonia. Objective: This study aimed to assess effects of intermittent theta-burst stimulation of the cerebellum on dystonia symptoms, quality of life, hand motor dexterity and cortical neurophysiology using transcranial magnetic stimulation. Methods: Sixteen participants with cervical dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 79 publications
2
36
0
2
Order By: Relevance
“…Noninvasive stimulation with transcranial direct current stimulation and transcranial magnetic stimulation led to slight short-term benefit in some studies. [26][27][28] Long-term improvement in dystonia has been reported after lesioning of the dentate nucleus. 23,24 Stimulation of the anterior cerebellar cortex has sometimes improved dystonic or athetoid movements in cerebral palsy, although typically a greater benefit reported in spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive stimulation with transcranial direct current stimulation and transcranial magnetic stimulation led to slight short-term benefit in some studies. [26][27][28] Long-term improvement in dystonia has been reported after lesioning of the dentate nucleus. 23,24 Stimulation of the anterior cerebellar cortex has sometimes improved dystonic or athetoid movements in cerebral palsy, although typically a greater benefit reported in spasticity.…”
Section: Discussionmentioning
confidence: 99%
“… 139 Another sham-controlled study involving a similar cerebellar TMS paradigm for 10 weeks combined with physical therapy also produced small but significant decreases (–10%) in TWSTRS motor scores and improvements in quality of life measures in 16 patients with cervical dystonia. 140 These studies are provocative because they imply that interventions involving the cerebellum may influence dystonic movements. On the other hand, a randomized sham-controlled study revealed no benefits after a single session of 1 Hz repetitive TMS over the cerebellum in 10 patients with writer’s cramp.…”
Section: Methodsmentioning
confidence: 99%
“…No differences were observed between rTMS followed by sensorimotor training in comparison to rTMS followed by massage and stretching in focal hand dystonia . In the only study of cervical dystonia in this category, neck motor training after real iTBS induced significant improvements in pain, quality of life, and hand dexterity in comparison to sham . The GRADE level for this category was rated as low.…”
Section: Resultsmentioning
confidence: 84%
“…Studies in this category tested some modality of motor training paired with neuromodulation methods ( n = 5), such as transcranial direct current stimulation (tDCS), repetitive transcranial magnetic stimulation (rTMS), or intermittent theta burst stimulation (iTBS) . Stimulation sites tested included the premotor cortex, primary motor cortex, and the cerebellum …”
Section: Resultsmentioning
confidence: 99%